Review on 3D Printed Bone Scaffold and Biocompatible Material - Nimisha, Shirbhate; Sanjay, Bokade (Journal of 3D Printing and Applications, 2020)
Bone Scaffold is a three-dimensional porous construction which provides support to promote natural cell growth in damaged or broken section of bone. In recent years researchers from various departments like biomedical, mechanical, orthopedics, have shown significant interest in adopting ‘Bone Scaffolds’ as a promising treatment for bone defects. ‘Bone Scaffold’ is a honeycomb-like architecture composes of bio-compatible material having grater advantages over current grafting solution. In this paper, the authors try to review the available e-articles in an organized way on the bone scaffold in the field of biomedical implants with 3D printing. The selected literature mainly focuses on the biocompatible material and various advanced manufacturing methods used for manufacturing / preparing of bone scaffolds. This article tries to padding the gap between theoretical and actual implementation of ‘Bone Scaffolds’ by properly analyzing selected research and allowing future opportunities for reinventing the new possibilities in the field of biomedical.
Keywords: 3D printing; biocompatible materials; Bone scaffold